Ab initio study of sodium intercalation into disordered carbon1. Issue 18 (14th May 2015) - Tsai, Ping-chun; Chung, Sai-Cheong; Lin, Shih-kang; Yamada, Atsuo
<x xml:space="preserve">Abstract</x> Larger interlayer distances and defects may account for both the sloping and flat regions of charge–discharge curves of disordered carbons.